Fundamental principles for preparing the CAST Key Reference Hard Disk : creating a reference drive to assist in the validation of a forensic disk imaging process /: creating a reference drive to assist in the validation of a forensic disk imaging process. (November 2016) - Barnes, Andrew
No abstract available